PENGARUH MODEL PEMBELAJARAN PENEMUAN TERBIMBING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Arditia, Maria Anggun Zahra; Yunarti, Tina; Setiawati, Santy (ALGORITMA: Journal of Mathematics Education, 2024)
AbstractThe point of this quasi experimental research was to find out the influence of inquiry learning models towards students mathematical representation abilities. The population was all students grade VIII of Junior High School State 5 Bandar Lampung in the academic year 2023/2024, which consisted of 323 students and were distributed into elevan classes. The sample in this study consisted of 28 students from class VIII-8 and 28 students from class VIII-9, who were selected using purposive sampling technique. The design was pretest posttest control group design. The data in this study were quantitative data obtained from tests on students' mathematical representation abilities. The data analysis technique included analyzing prerequisites and hypotheses using Independent Sample T-Test (t-test). The research findings indicated that the average score improvement (gain) of students' mathematical representation abilities who followed the guided inquiry learning model was higher than the average score improvement (gain) of students' mathematical representation abilities who followed conventional learning. Therefore, the use of guided inquiry learning model influenced students' mathematical representation abilities. The inqury learning model should have been considered by teachers in the learning process to enhance students' mathematical representation abilities.AbstrakPenelitian eksperimen semu ini bertujuan untuk mengetahui pengaruh model pembelajaran penemuan terbimbing terhadap kemampuan representasi matematis siswa. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 5 Bandar Lampung semester genap tahun pelajaran 2023/2024 sebanyak 323 siswa yang terdistribusi ke dalam 11 kelas yaitu kelas VIII-1 sampai VIII-11. Sampel dalam penelitian ini adalah siswa kelas VIII-8 terdiri dari 28 siswa dan VIII-9 terdiri dari 28 siswa yang terpilih dengan teknik purposive sampling. Desain yang digunakan adalah pretest posttest control group design. Data penelitian ini berupa data kuantitatif yang diperoleh dari tes kemampuan representasi matematis siswa. Teknik analisis data meliputi analisis uji prasyarat dan uji hipotesis menggunakan Independent Sample T-Test (uji-t). Hasil penelitian menunjukkan bahwa rata-rata skor peningkatan (gain) kemampuan representasi matematis siswa yang mengikuti model pembelajaran penemuan terbimbing lebih tinggi daripada rata-rata skor peningkatan (gain) kemampuan representasi matematis siswa yang mengikuti pembelajaran konvensional. Dengan demikian, penggunaan model pembelajaran penemuan terbimbing berpengaruh terhadap kemampuan representasi matematis siswa. Model pembelajaran penemuan terbimbing hendaknya dijadikan sebagai alternatif dalam proses pembelajaran oleh guru untuk meningkatkan kemampuan representasi matematis siswa.